Kinetics of Cardiac Output at the Onset of Exercise in Precapillary Pulmonary Hypertension. (20th November 2016) - Lador, Frédéric; Bringard, Aurélien; Bengueddache, Samir; Ferretti, Guido; Bendjelid, Karim; Soccal, Paola M.; Noble, Stéphane; Beghetti, Maurice; Chemla, Denis; Hervé, Philippe; Sitbon, Olivier
Abstract : Purpose. Cardiac output (CO) is a cornerstone parameter in precapillary pulmonary hypertension (PH). The Modelflow (MF) method offers a reliable noninvasive determination of its beat-by-beat changes. So MF allows exploration of CO adjustment with the best temporal resolution. Methods. Fifteen subjects (5 PH patients, 10 healthy controls) performed a submaximal supine exercise on a cycle ergometer after 5 min of rest. CO was continuously determined by MF (C O M F ). Kinetics of heart rate (HR), stroke volume (SV), and CO were determined with 3 monoexponential models. Results. In PH patients, we observed a sudden and transitory drop of SV upon exercise onset. This implied a transitory drop of CO whose adjustment to a new steady state depended on HR increase. The kinetics of HR and CO for PH patients was slower than that of controls for all models and for SV in model 1. SV kinetics was faster for PH patients in models 2 and 3. Conclusion. This is the first description of beat-by-beat cardiovascular adjustments upon exercise onset in PH. The kinetics of HR and CO appeared slower than those of healthy controls and there was a transitory drop of CO upon exercise onset in PH due to a sudden drop of SV.